Réseaux de chercheurs en Méditerranée. Contraintes institutionnelles et autonomie scientifique - François Siino (L’Année du Maghreb)
For over a decade, research networks have become one of the most visible forms of international scientific cooperation. Between Northern and Southern shores of the Mediterranean, networks have superseded traditional forms of cooperation based on flows of people. One of the largest of these networks, the Ramses Network of Excellence in human and social sciences was created in 2006 with European funding support. Through the experience of scientific cooperation, this article analyzes the role of researchers for inscribing such a network onto the European agenda. The article further attempts to assess the extent to which such cooperation may herald the development of an autonomous Mediterranean scientific space vis-à-vis of the national and european political authorities.